Growth Spillover Effect Pada Kawasan Germakertosusila Plus: Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi Tahun 2014-2023 - Risma Dea Ramadhani; Annis Nurfitriyana Nihayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Germakertosusila Plus region recorded the lowest economic growth and the highest poverty rate in Central Java in 2014-2023. This study aims to identify the growth spillover effect between 15 districts/cities and analyze the factors that influence economic growth in the region. Using the VECM method and East Java BPS data, the results show a spillover effect between regions. In the short term, the population and spillover effect variables have a positive but insignificant effect, government spending and minimum wages have a positive and significant effect. In the long term, the population has a positive and significant effect, the government spending, minimum wages and spillover effect variables have a negative and significant effect on economic growth.